Modeling of fire suppression in the ecological system of tress and shrubs - Beketova, G.M. (Математичне моделювання в економіці, 2017)
This work presents an approach to mathematical modeling of directional suppression of fires in the ecosystem of trees and shrubs. It is taken into account that for effective extinguishing of fire in the natural ecosystem is necessary to ensure a uniform and strong impact of dispersed flow over the entire area of the hearth burning. The presented model can be used as a baseline when planning measures of prevention, localization and liquidation of fires in natural ecosystems near industrial centers. This approach will prevent the development of fire and environmental pollution by combustion products. У роботі представлений підхід до математичного моделювання спрямованого гасіння пожеж в екосистемі дерев і кущів. Враховано, щодо ефективного гасіння пожежі в природній екосистемі необхідно забезпечити рівномірний і досить потужний вплив дисперсного потоку по всій площі горіння вогнища. Представлена модель може бути використана в якості базової при плануванні заходів попередження, локалізації і ліквідації пожеж у природних екосистемах поблизу промислових центрів. Даний підхід дозволить попередити розвиток пожежі і забруднення навколишнього середовища продуктами горіння. В работе представлен подход к математическому моделированию направленного тушения пожаров в экосистеме деревьев и кустов. Учтено, относительно эффективного тушения пожара в природной экосистеме необходимо обеспечить равномерное и довольно мощное влияние дисперсного потока по всей площади очага горения. Представленная модель может быть использована в качестве базовой при планировании мер по предупреждению, локализации и ликвидации пожаров в природных экосистемах вблизи промышленных центров. Данный подход позволит предупредить развитие пожара и загрязнения окружающей среды продуктами горения.